ANALYSIS OF DEVIATION BEHAVIOR IN THE SMAN 2 ABIANSEMAL BUILDING WITH THE SRPMK SYSTEM AND FLAT SLAB - I Made Dwi Permana Putra; Ni Komang Ayu Agustini; I Gusti Agung Putu Eryani (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2025)
The development of educational infrastructure in seismically active regions demands structural systems that ensure both safety and functionality. This study evaluates the structural performance of the SMAN 2 Abiansemal building by comparing two structural systems: the conventional Special Moment Resisting Frame (SRPMK) and a flat slab system with drop panels. Finite element analysis using ETABS and dynamic response spectrum methods, as stipulated in SNI 1726:2019, was employed to assess inter-story drift and total displacement. The SRPMK system demonstrated stable behavior, with maximum drift values remaining below the permissible limit of 62.77 mm. In contrast, the flat slab system initially exceeded this threshold due to its lower lateral stiffness. A design revision increasing the column dimensions from 45×45 cm to 50×50 cm successfully reduced the drift values to compliant levels. Although the flat slab system requires dimensional adjustments, it offers architectural and construction benefits, making it a viable alternative for mid-rise educational buildings in seismic-prone areas. The study emphasizes the importance of dynamic drift analysis and early-stage design validation when adopting beamless slab configurations in earthquake-sensitive zones.